Black Bodies at the Dangerous Intersection of Gender Violence and Mass Criminalization. Issue 7 (9th August 2021) - Richie, Beth E.; Eife, Erin
ABSTRACT: While considerable attention has been given to the ways that intimate partner violence impacts women, the prevailing analyses have not sufficiently attended to the range of social consequences that have particularly deleterious effects on marginalized groups. Part of what is missing in this analytical gap is attention to the negative effect of racialized criminalization and incarceration of women who have experienced gender-based violence. For this reason, this article will make the link between gender violence against Black women and the forces that have led to their overcriminalization. Following a brief review of the current statistics on rape, battering, stalking, emotional manipulation, and other forms of abuse, we will present data on arrest and incarceration rates of Black women in the U.S. Then, a case history will be used to illustrate how the two dangerous trends are linked. The article will conclude with theoretical analyses of the linkages and strategic recommendations for change.